A Bibliometric Analysis of Audit Report Lag, Cost of Equity Capital, and Information Asymmetry - Arifin, Luthfia Sari; Koeswayo, Poppy Sofia; Yunita, Devianti (JURNAL MANAJEMEN MOTIVASI, 2025)
This research emerged due to the increasing concern over audit timeliness and its influence on financial market behavior, particularly the cost of equity capital and the degree of information asymmetry. Finding, characterizing, and analyzing the evolution of research publishing trends investigated by scholars globally is the primary goal of this bibliometric study. Using a systematic review approach, researchers gathered 98 documents from the Scopus database published between 2019 and 2024. The findings indicate a noticeable growth in academic publications focusing on audit report lag and its implications for transparency, investor confidence, and financial decision-making. These articles include topics such as auditor competence, audit committee effectiveness, governance structures, and country-level regulatory impacts. The increase in publication volume is influenced by data accessibility, collaborative research funding, and global scholarly interest in audit efficiency and financial risk management. This study offers several recommendations to enhance organizational knowledge related to improving audit timeliness, mitigating information asymmetry, and reducing equity financing costs.